An Analysis of the Insurance Market in the Czech Republic - Černohorská, Liběna; Klofát, Matěj (EDP Sciences - Web of Conferences, 2021)
Research background: We are currently witnessing significant changes in traditional values and developments concerning the globalization of the financial markets. Since the beginning of the 21st century, not only have the instruments used by global financial markets changed significantly, but the way they operate and the behavior of their participants have changed as well. Digitalization and the use of modern technologies are gradually beginning to take hold in all segments of the global economy. In the field of insurance, this mainly concerns the areas of insurance distribution and claims settlement. Purpose of the article: The purpose of this paper is to analyze the insurance industry in the Czech Republic for the period of 2014 to 2018. Methods: Spider analysis was used to conduct the analysis. This type of analysis is a comprehensive analytical tool, which can also be used by the management of commercial insurance companies; it is based on 16 ratios, which are divided into four segments. Spider analysis provides a clear representation of the examined company’s position in comparison with the market average or with competing companies in that field of business. Using spider analysis, it is possible to portray the insurance market in the Czech Republic using the selected insurance companies. Findings & value added: Based on the analysis results, it was found that Pojišťovna VZP was the only company that differed from the other commercial insurance companies analyzed – and the insurance market as a whole. Globalization’s effects on developmental trends in the world’s economies, the financial markets, and the business activities of both commercial insurance companies and the insurance industry are significant and difficult to estimate in terms of scope.
Analýza pojistného trhu v České republice
Keywords: financial market; insurance; insurance company; spider analysis; finanční trh; pojištění; pojišťovna; spider analýza